Historically Heavy Rainfalls in Singapore on 19 November 2009 and 17 July 2010 - Katsura, Hidemitsu (Asian Journal of Chemistry, 2012)
On 19 November 2009 and 17 July 2010, historically heavy rainfalls occurred in Singapore. Aerosol samples (PM 4.5) were collected with a sampling pump at a flow rate of 5 L per min from 16 to 22 November 2009, from 08 to 20 February 2010 and from 16 to 28 July 2010. Rainwater samples were collected every 5 mL of rainfall using an Horiba Raingoround sampler from 17 to 21 November 2009, from 10 to 18 February 2010 and from 16 to 28 July 2010 on a rooftop at the National University of Singapore in Singapore. These samples were analyzed by ion chromatography for anions and by gas chromatography-mass spectrometry for nitrogen and oxygen stable isotope ratios. During periods of historically heavy rainfall, the d18O/16O ratios in nitric-oxide substances in aerosols tend to decrease tremendously. The 14N atoms in nitrogen oxide ions in rain drops are converted to 14C through neutron-activated nuclear chemical reactions at higher altitudes. Consequently, d15N/14N ratios increase with the production altitudes of rain drops. Therefore, figures displaying the d15N/14N ratios of nitrogen oxide ions in different separated rainfall fractions have a characteristic form. This implies that there is some relationship between the chemical characterization of aerosols and the chemical characterization of rainfall.